Pengaruh Dimensi Organisasi, Kepemimpinan, Motivasi terhadap Transfer of Knowledge dan Daya Saing Organisasi (Studi pada Bank Niaga Makasar) - St.Sukmawati S.; Armanu Thoyib; Margono Setiawan; Surachman - (Jurnal Aplikasi Manajemen, 2012)
The objective of this research is to study the process transfer of knowledge and its about on organizational competitiveness, in this case Bank Niaga Makassar. The respondents are from middle management, lower management (supervisors) and the rank-and-file (employees). The collected data is analyzed using Structural Equation Modeling (SEM) using AMOS computer software (Analysis of Moment Structure) version 5.0. The findings of this research are: (1) the organizational dimension having significant impact on the process transfer of knowledge is organizational objective, while formalization has negative impact and organizational culture has no significant impact; (2) leadership also has an impact on the process transfer of knowledge in the organization, (3) motivation has significant impact on transfer of knowledge in the organization under study, and (4) transfer of knowledge will have significant direct impact on organizational competitiveness.Keywords: organizational dimensions, leadership, motivation, transfer of knowledge, organizational competitiveness.